STRUKTUR DAN KOMPOSISI VEGETASI BAWAH RIPARIAN SUNGAI BATANG KUANTAN KABUPATEN KUANTAN SINGINGI SEBAGAI IMPLEMENTASI BUKU SAKU KEANEKARAGAMAN HAYATI - Muhammad Iqbal Ramdani; Nursal Nursal; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the structure and composition of lower vegetation found in the riparian area of Batang Kuantan River, Kuantan Singingi Regency. And implement it in the design of a pocket book on biodiversity material. This research is descriptive in nature, conducted in April-May 2019, and the data collection method is by survey. Determination of the location of the study was carried out by means of purposive random sampling, namely the determination of the location seen based on the existing environmental bases such as the physical condition of the river, the speed of the river current, topographic shape and human activities so that it obtained 4 research stations. The parameters observed in this study include biological parameters as well as environmental chemistry parameters. The results obtained showed that under vegetation in riparian areas in the Batang Kuantan River found 19 plant families, 24 species and 1365 individuals. Based on the highest important value index (INP) found in Colocasia esculenta species with a value of 34.76%. The vegetation diversity index found in the riparian region of the Batang Kuantan river is categorized into a moderate level with values ranging from 1.20-1.91. The physical-chemical conditions in the Batang Kuantan river riparian area are categorized as good to support the life of lower vegetation in the Batang Kuantan River. The results of the research that has been carried out are implemented into a pocket book design on biodiversity material in high school grade X which can later be used in the process of learning biology in schools.Key Words:Structure of Vegetation, Composition, The Under Vegetation, Batang Kuantan River, Pocket Book.